A consistent soot nucleation model for improved prediction of strain rate sensitivity in ethylene/air counterflow flames. Issue 7 (3rd July 2022) - Quadarella, Erica; Guo, Junjun; Im, Hong G.
Abstract: An improved consistent soot nucleation model was proposed and tested on ethylene counterflow flames at different strain rates. The main objective of the proposed model is to capture the correct strain rate sensitivity and broaden the applicability of the aerosol part of the soot model with different gas-phase kinetic mechanisms. Due to the uncertainties associated with experimental measurements of quantitative soot volume fraction (SVF), the approach's effectiveness is mainly investigated on qualitative behavior in terms of strain rate sensitivity. Starting from a dimer-based nucleation model available in literature, soot inception is described as heterogeneous collisions of polycyclic aromatic hydrocarbons (PAHs) forming an intermediate dimer. Such a model justifies the inclusion of small precursors that conciliate a satisfactory reproduction of SVF sensitivity to strain rate, while retaining the quantitative accuracy of SVF prediction. The nucleation and condensation rates sensitivities are found to be regulated by the presence of the dimer to maintain the right balance with the upstream dimerization process. The heterogeneous collision model helps generalize the procedure and makes the model more adaptable to different kinetic mechanisms. Details about the inclusion of temperature-dependent sticking coefficients are also provided and found to be pivotal for a correct synergistic prediction of SVF trends and PAHs sensitivities to strain rate. The integration of important features in the soot nucleation model allows a generalized soot model free of empirical corrective factors, capturing the correct sensitivity to strain rates. Its ease of implementation and low computational cost make it suitable for turbulent flame simulations. Copyright © 2022 American Association for Aerosol Research